2018
DOI: 10.1063/1.5041485
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluidic terahertz metasensor for sensing in aqueous environment

Abstract: The terahertz spectral region has received tremendous attention for label free chemical and biological sensing, due to the presence of molecular fingerprints, low energy characteristics, and remote sensing capabilities. However, a major hindrance for the realization of a high performance terahertz bio-chemical sensor comes from the large absorption of terahertz waves by aqueous solution. Here, we overcome this limitation by confining the analyte-aqueous solution in a nanovolumetric fluidic chamber, integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 58 publications
(61 reference statements)
2
57
0
Order By: Relevance
“…The IPA-water mixtures with the IPA percent of 100%, 75%, 50%, 25% and 0% were tested (100%-pure IPA, 0%-pure water). The refractive index and the absorption coefficient of the IPA-water mixture decrease with the increase of the IPA concentration [22], [26]. For comparison, the IPA-water mixtures were also measured based on the MM with one big channel.…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IPA-water mixtures with the IPA percent of 100%, 75%, 50%, 25% and 0% were tested (100%-pure IPA, 0%-pure water). The refractive index and the absorption coefficient of the IPA-water mixture decrease with the increase of the IPA concentration [22], [26]. For comparison, the IPA-water mixtures were also measured based on the MM with one big channel.…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…In the previous studies, the analyte is usually located in the whole area of the MM and the volume of the analyte is large [5][6][7][8][9][10][11][12][13][14][15][16][20][21][22][23][24][25][26][27]. If we don't consider the required sample volume, the resonance frequency shift per unit refractive index change in our study (72 GHz/RIU for the multichannel design, 223 GHz/RIU for the one big channel design) is comparable to previous studies (such as, 40 GHz/RIU [13], 220 GHz/RIU [20], 305 GHz/RIU [21]).…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…It can be observed that the trend of the Q ‐factor at ω 1 shows a linear increase with a maximum value of 50. The abovementioned electromagnetic performance is better than that obtained for other THz‐metamaterial devices reported in the literature . This result can be explained by the field distributions for the PSM in the TE and TM modes, as shown in Figure c.…”
mentioning
confidence: 61%
“…However, these approaches are limited to certain applications owing to symmetric or asymmetric split‐ring resonator configurations. Moreover, tunable THz metamaterials reported in the literature are limited to low Q ‐factors (≈0.5–5) and require complicated fabrication processes . Meanwhile, fabrication is mostly completed on Si, III–V materials, and quartz substrates, which strictly limits their possible applications, such as applications that have a requirement for a curved surface.…”
mentioning
confidence: 99%
“…Therefore, the nanofluidic platform is developed for THz sensing in the aqueous environment. In Figure h, selective sensing of adenosine triphosphate (ATP) was demonstrated through aptamer functionalization on Au metallic metamaterial patterns, which allows in vivo monitoring of bioprocess in the aqueous environment …”
Section: Metamaterials In Chemical Sensing Applicationsmentioning
confidence: 99%